Resistência de variedades de soja à Heliothis virescens (Lepidoptera: Noctuidae) - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The tobacco budworm Heliothis virescens in recent harvests have caused damage in soybeans. Traditionally, the most widely used for its control method it is that promotes the chemical imbalance in the environment, and the appearance of resistant pest insecticides. Therefore it is necessary to search for sustainable control alternatives, the aim of this study is to evaluate the resistance of soybean varieties to H. virescens. Experiments were conducted in the Agricultural Entomology Laboratory of Instituto Federal Goiano - Campus Urutaí under controlled conditions of temperature, humidity and photoperiod. The varieties used in the trials were P 98Y30 RR, NA 7337 RR, SYN 1163 RR, NK 7059 RR, ANTA 82 RR, M 7110 IPRO (Bt), BRS 8160 RR, BRSGO Jataí, IAC 100. In the first trial was evaluated the attractiveness to 3rd instar caterpillars with food, getting the crawler number attracted by leaf disc at different times, consumption and the attractiveness index with and without choice test. NK 7059 RR variety was the most attractive obtaining also the largest leaf consumption, showing susceptibility to H. virescens. Already IAC 100 showed behavior similar to having resistance range M 7110 IPRO. In the second trial evaluated the antibiosis to H. virescens soybean varieties variables were assessed period, viability of the larval stage and weight caterpillars to ten days of age, period and pre-pupal viability, period, viability and pupal weight 24 hour age period, and total survival and longevidade.de adults. The BRS 8160 RR varieties, BRSGO Jataí, P 98Y30 RR were highly susceptible to H. virescens, and IAC 100 and M 7110 IPRO showed antibiosis resistance type. These soybean cultivars can be directly used by famers or by breeders as donor sources in the breeding program for resistance to Heliothis virescens.
Keywords: antibiose; antixenose; lagarta-da-maçã do algodoeiro; interação inseto planta; resistência de plantas a insetos; antibiosis; antixenosis; tobacco budworm; insect plant interactions; insect resistance to plants.; CIENCIAS AGRARIAS